Microarrays Preparation, Microfluidics, Detection Methods, and Biological Applications - Dill, Kilian; Liu, Robin Hui.; Grodzinski, Piotr; SpringerLink (Online service) (New York, NY : Springer New York, 2009)
The area of microarrays has evolved from genomics, and has been applied to proteomics and single cell studies as well. The applications of microarrays benefit diverse fields ranging from fundamental systems biology to practical diagnostic tests. This book provides a critical analysis of the applications of microarrays in several key areas of bioanalytical research including DNA studies, peptide arrays, protein arrays, combinatorial chemistry arrays, cell-based arrays, and glycoarrays. Further progress in microarrays is being spurred by the advances in micro- and nano-fabrication technologies, modern molecular biology, and data mining. This book is designed to be a useful source of fundamental and current information for microarray research practitioners and for those who are just entering this field.
Overview and New Detection Method -- The Current Status of DNA Microarrays -- Electrochemical Detection on Microarrays -- Fluidic Manipulation and Microarrays -- Fully Integrated Microfluidic Device for Direct Sample-to-Answer Genetic Analysis -- Integrated Microfluidic Devices for Automated Microarray-Based Gene Expression and Genotyping Analysis -- Statistical Data Evaluation on Microarrays -- Intensity Concentration Relationships for Electrochemical Detection -- Applications -- Genotyping Arrays -- Peptide-Based Microarray -- Protein Microarrays for the Detection of Biothreats -- Photo-Generation of Carbohydrate Microarrays -- Expression Profiling Using Microfluidic Living Cell Arrays -- New Approaches to the Synthesis of Addressable Microarray Molecular Libraries -- eSensor®A Microarray Technology Based on Electrochemical Detection of Nucleic Acids and Its Application to Cystic Fibrosis Carrier Screening -- Future Improvements in Microarray Sensing -- Use of Redox Enzymes for the Electrochemical Detection of Sequence-Specific DNA and Immunochemical Entities -- Biochip Platforms for DNA Diagnostics -- MagArray Biochips for Protein and DNA Detection with Magnetic Nanotags: Design, Experiment, and Signal-to-Noise Ratio -- Bar Coding Platforms for Nucleic Acid and Protein Detection -- Electrochemical Nanoparticle-Based Sensors.
Keywords: Chemistry; Analytical chemistry; Biotechnology; Biochemical engineering; Electrochemistry; Chemical engineering; Materials science; Chemistry; Analytical Chemistry; Biotechnology; Biochemical Engineering; Electrochemistry; Industrial Chemistry/Chemical Engineering; Characterization and Evaluation of Materials; Electronic books